O17 Effectiveness of rituximab in the treatment of neuro-psychiatric SLE: results from the British Isles Lupus Assessment Group Biologics Register. (26th April 2021) - David, Trixy; Hum, Ryan Malcolm; Sutton, Emily; Parker, Benjamin; McCarthy, Eoghan; Bruce, Ian N; ,
Abstract: Background/Aims   Neuro-psychiatric (NP) involvement in systemic lupus erythematosus (SLE) can occur in 56.3% cases. Rituximab (RTX) has been demonstrated to be safe and efficacious in the treatment of refractory SLE although there is limited evidence for its use in NP-SLE. We aim to describe the baseline characteristics and short-term effectiveness of RTX in patients treated for NP-SLE within the British Isles Lupus Assessment Group Biologics Register (BILAG-BR). Methods   Patients with active NP involvement; scoring BILAG A or B and/or on SLEDAI-2K were included. Baseline characteristics, disease activity and oral steroid dose pre and 5 - 9 months post-treatment were analysed. Paired Wilcoxon-Signed-Ranked Test was used to determine changes in disease activity scores and steroid dose. Results   We identified 74 patients of whom 61 (82%) were female and 48 (74%) Caucasian. Median age [interquartile range (IQR)] was 45.5 years [37 - 58] and disease duration 11.5 years [7 - 18.8]. 68 patients had active disease on BILAG (A = 34, B = 34) with 6 scoring on SLEDAI-2K only. The majority (n = 71/74, 96%) had at least one other organ involved. Central nervous system (CNS) disease occurred in 45/65 (69%) cases, 12/65 (18%) had peripheral nervous system (PNS) disease and 8/65 (12%) CNS/PNS overlap. Anti-Ro was the commonest identified antibody (n = 26/57, 46%) and 42 of 59 (71%) patients had a raised anti-dsDNA and/or low complement. The majority (n = 64/74, 86%) were taking glucocorticoids and median prednisolone dose was 15mg [IQR 10 - 20]. Pre and post-RTX BILAG, total SLEDAI-2K and oral steroid dose were available in 50, 57 and 27 patients respectively. Following RTX, patients with NP BILAG A or B reduced from 50 to 11 (p < 0.0001). 4 of the 6 patients with NP-SLE on SLEDAI-2K alone, improved. Total median SLEDAI-2K score reduced from 12 [IQR 14 - 18] to 2 [IQR 0 - 4] (p < 0.0001). Median steroid dose reduced from 15mg [IQR 11.3 - 25] to 10mg [IQR 6.9 - 18.8] (p = 0.009). For 53 patients, active CNS, PNS and overlap disease reduced from 37 (70%) to 6 (11%), 10 (19%) to 3 (6%) and 6 (11%) to 4 (8%) respectively. In 9 patients treated with concomitant CYC, none had persistent NP disease. In contrast, 11 of 41 patients who had RTX alone had persistent NP disease. Conclusion   RTX use is associated with improvement in NP-SLE with reduction in oral steroid dose. Concomitant CYC may enhance the level of improvement seen with RTX. Large scale studies are therefore warranted to establish the effectiveness of RTX alone or in combination with CYC in the treatment of NP-SLE. Disclosure   T. David: None. R. Hum: None. E. Sutton: None. B. Parker: None. E. McCarthy: None. I. Bruce: None.